2011
DOI: 10.3892/etm.2011.411
|View full text |Cite
|
Sign up to set email alerts
|

miRNA expression profile in primary gastric cancers and paired lymph node metastases indicates that miR-10a plays a role in metastasis from primary gastric cancer to lymph nodes

Abstract: Abstract. The aim of this study was to identify and evaluate microRNAs (miRNAs) in gastric cancer lymph node metastasis. A miRNA array was used to compare the expression of miRNAs in primary gastric cancer and paired lymph node metastases. miRNAs found to be differentially expressed were validated in a cohort of primary gastric cancer tissues, and the relationship between expression and the clinicopathological characteristics of the specimens was analyzed. The expression level of miR-10a in a gastric mucosal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 27 publications
3
52
0
Order By: Relevance
“…However, Weidong Chen et al investigated the expression of miR-10a in 33 GC cases and observed that miR-10a expression was higher in GC tissues than in the adjacent tissues [22]. The inconsistency may be a result of the different quantity of clinical samples and the indistinctive change of miR-10a in GC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, Weidong Chen et al investigated the expression of miR-10a in 33 GC cases and observed that miR-10a expression was higher in GC tissues than in the adjacent tissues [22]. The inconsistency may be a result of the different quantity of clinical samples and the indistinctive change of miR-10a in GC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that miRNAs play an important role in the regulation of key drivers of cancer, as well as drug resistance (Sorrentino et al, ; Yang et al, ; Kumar et al, ; Iorio and Croce, ; Kuang et al, ) and metastasis (Bracken et al, ; Foekens et al, ; Le et al, ; Chen et al, ; Imam et al, ), the ability to selectively target miRNAs in cancer is an attractive prospect for drug design. miRNAs in regions of chromosomal loss may be restored by miRNA mimics and miRNAs in regions of amplification may be suppressed by miRNA inhibitors.…”
Section: Mirna In the Clinicmentioning
confidence: 99%
“…Metastatic potential of gastric cancer cells have been associated with changes in the expression profile of miRNAs involved in regulating Wnt signaling pathway. MiR-10a upregulation and miR-516a-3p decreased expression were proven to play a pivotal role in tumor invasion and metastasis from primary gastric cancer to lymph nodes or peritoneum, respectively [168,169] . Using proteomics approaches, Takey et al [169] showed that miR516a-3p targets extracellular sulfatase 1 (HSulf-1).…”
Section: Role Of Micrornas In Wnt/b-catenin Signaling In the Gastric mentioning
confidence: 99%
“…Homeostasis of the gastrointestinal epithelium is 87 [47,[69][70][71][72][73][74][75]232] Fzd-3 [78] CTNNB1 [9,[88][89][90][91][92][93]96,97] LRP6 [228] TCF7L2 [98][99][100] PPN [79] CDH17 [80] EZH2 [81] HMGA1, HMGA2 [210,211] YY1 [86] TC1 (C8orf4) [201,202] miR-17-92 [161] mir-10a [168] has-miR-335 [166] hsa-miR-375 [163] Downregulation or function inhibition in gastric cancer Downregulation by hypermethylation Inactivation by miRNAs APC [145,146] APC [175] sFRP1, sFRP2, sFRP4, sFRP5 [78,96,149] AXIN2 [159] WIF-1 [144,149] EZF1 [78] Dkk-1, Dkk-2, Dkk-3 [59,144,148,…”
Section: Wnt/b-catenin Pathway In Gastric Carcinogenesismentioning
confidence: 99%